IMPLEMENTASI KOMPETENSI FUNGSIONAL DALAM PELAKSANAAN PENGADAAN BARANG DAN JASA PADA BAGIAN PENGADAAN BARANG DAN JASA SEKRETARIAT DAERAH KABUPATEN PROBOLINGGO - Af’idah, Af’idah (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2024)
The aim of this research is to realize the implementation of functional competence in the procurement of goods and services in the goods and services procurement section of the regional secretariat of Probolinggo Regency. The research method used is descriptive research with a qualitative approach. This research used six informants. The results of the research are four factors that strengthen the implementation of functional competence in the procurement of goods and services, including resources, communication, bureaucracy and attitudes. The implementation of functional competence in the procurement of goods and services in Probolinggo Regency has been implemented but is not yet optimal. Weak coordination between procurement actors and a lack of BPBJ personnel who have passed competency tests have an impact on procurement implementation. Factors that influence the level of success in implementing the procurement of goods and services include the quality of human resources in accordance with recommendations, provision of facilities and infrastructure for managing goods and services, communication both internally and externally as well as appropriate procurement planning.